Cartas de Georg Büchner: processos de criação em dramaturgia - Toscano, Antonio Rogério (2019)
This work‟s goal is to comprehend how the writing of letters by German playwright Georg Büchner can be taken as a relational source to establish a productive critique of the creative processes of theater works – and extra theatrical ones – by the author. Placed on a non-dramaturgic nor artistic field, such letters, written to family and friends, contain reflections and approaches which can be considered work materials for a rigorous study of the process of scenic creation of his writings, some of them also unfinished, produced in the first half of the 19th Century, and which defined a profound influence over the contemporary creation of dramaturgy. This research also seeks to make evident, as a hypothesis, how those writings become, today, unavoidable sources for the establishment of creative authorship processes in the theater staging of such works, especially when held in pedagogical contexts – in which said works were laboratory experimented and constituted themselves as foundations for the scenic creation, and also to the proposition of this research. Each letter is, here, studied in confrontation with the production period of his works, and from stablished relations, formal and substantial dimensions for the scenic approach to such materials are sought to be extracted. Creative processes conducted alongside apprentices - in theater schools such as Escola Livre de Teatro de Santo André (Free School of Theater of Santo André), Escola de Arte Dramática (School of Dramatic Arts), and the graduation course of Comunicação das Artes do Corpo da Pontifícia Universidade Católica de São Paulo (Body Arts Communication of Catholic Pontifical University of São Paulo) – titled “devoração da cobaia WoyZÉck - um experimento-máquina” (devourment of the WoyZÉck guinea pig – a machine-experiment), “Eu-Büchner” (I-Büchner), “O preceptor” (The preceptor), and “Somos muito solitários” (We are very lonely), were taken as contemporary pedagogical-theatrical scenes marked by the articulation of sense, from the intertwining of the author‟s voices expressed in his letters; therefore, studied as a central subject for the creation, and capable of emulating authorship reinterpretations by the actors-creators